Treatment patterns and clinical outcomes in high‐risk newly diagnosed multiple myeloma patients carrying the 17p deletion: An observational multi‐center retrospective study. Issue 6 (28th April 2018) - Cohen, Yael C.; Saranga, Avi; Gatt, Moshe E.; Lavi, Noa; Ganzel, Chezi; Magen, Hila; Avivi, Irit; Tadmor, Tamar; Suriu, Celia; Jarchowsky Dolberg, Osnat; Papushado, Amitai; Trestman, Svetlana; et al.
Abstract: Del17p is a genomic imbalance occurring in ∼7%‐10% of myeloma at diagnosis newly diagnosed myeloma patients (NDMM) and comprises a poor prognostic factor. The goal of this study is to analyze real world data and outcomes among NDMM patients carrying 17p deletion. We report an observational, retrospective, multicenter study. Sixty consecutive patients diagnosed with multiple myeloma in the 8 participating centers diagnosed between 1/2008 and 1/2016 proven to carry 17p deletion by means of fluorescence in situ hybridization (FISH) were identified. Most received a bortezomib‐based induction, over half underwent autologous hematopoietic cell transplantation (HCT); 30% of the patients gained early access to new novel agents via clinical trials, access programs or private insurance. Overall response rate (ORR) after induction was 85%; 94% for transplant eligible (TE); and 75% for transplant ineligible (NTE), and declined in subsequent treatment lines, 64% achieved ≥ VGPR. Median overall survival (OS) was 43 months; median progression free survival (PFS) was 11 months, 19 months for TE and 7 for NTE. In multivariate analysis: higher M‐Spike, presence of extramedullary disease, and >50% of cells baring del17p were associated with adverse PFS; Autologous HCT and higher hemoglobin were associated with longer PFS; OS was 59 months for patients with early access to newer agents. Older age and higher M‐Spike levels were associated with adverse OS, Autologous HCT was associated with favorable OS, 59.7 vs 28.7 months for NTE patients. Despite the improvement achieved with autologous HCT and new novel agents, the prognosis of patients with 17p deletion is still inferior, emphasizing the need for novel approaches.